2022
DOI: 10.3390/en15103752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Catenary Distributed Parameters on the Resonance Frequencies of Electric Railways Based on Quantitative Calculation and Field Tests

Abstract: High-order harmonic resonance is a key issue in the traction power supply systems (TPSS) of electric railways for safe operation. The effective evaluation of the resonance frequency is critical for taking measures to suppress harmonic resonance. In this paper, the influence of the distributed parameters of traction networks on resonance frequencies based on accurate calculation is proposed. The quantitative assessments of the distributed impedance and admittance are investigated. Furthermore, the theoretical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The interaction between the public power system and the traction power supply system is modeled as a simple Thevenin-and Norton-equivalent interaction, respectively, assuming the distortion of the trains as a source for the disturbances in the public grid. Other examples of ERPS modeling for resonance and distortion studies can be found for the analysis of the harmonic sources [112], impedance identification [113,114], harmonic penetration to the local power supply of the traction substation [115], filter design [116], improved propagation studies [114][115][116], etc.…”
Section: Modeling the Waveform Distortion Interactions In Railway Sys...mentioning
confidence: 99%
“…The interaction between the public power system and the traction power supply system is modeled as a simple Thevenin-and Norton-equivalent interaction, respectively, assuming the distortion of the trains as a source for the disturbances in the public grid. Other examples of ERPS modeling for resonance and distortion studies can be found for the analysis of the harmonic sources [112], impedance identification [113,114], harmonic penetration to the local power supply of the traction substation [115], filter design [116], improved propagation studies [114][115][116], etc.…”
Section: Modeling the Waveform Distortion Interactions In Railway Sys...mentioning
confidence: 99%